2010
DOI: 10.1149/1.3276095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citrate Additive on Transparency and Photostability Properties of YVO[sub 4]:Bi[sup 3+],Eu[sup 3+] Nanophosphor

Abstract: YVnormalO4:normalBi3+,normalEu3+ nanoparticles were prepared by the wet chemical synthesis in various concentrations of sodium citrate, 15⩽xcit⩽90 , where xcit is the nominal molar percentage of citrate relative to the sum of metallic ions, Y3+ , Bi3+ , and Eu3+ . Mean primary nanoparticle diameter and mean hydrodynamic size in the aqueous colloidal solution have minimum values, 21 and 36nm , respectively, for the sample prepared at xcit=50 . The transparency of the aqueous colloidal solution in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…This result indicates that the amount of citrate ions relative to that of vanadate ions is the predominant factor for determining the photobleaching property. This also supports that the photobleaching behavior of YVO 4 :Bi 3+ ,Eu 3+ nanophosphor originates from the photochemical redox reaction between the citrate ions and V 5+ in YVO 4 host crystal and hence the formation of V 4+ and oxygen vacancies, as discussed in our previous work [1]. In addition, the gradual recovery of the normalized PL intensity might be attributed to the oxidation of V 4+ to V 5+ after the photochemical decomposition of citrate ions.…”
Section: Relation Between Citrate Ions and Photobleaching Behaviorsupporting
confidence: 90%
“…This result indicates that the amount of citrate ions relative to that of vanadate ions is the predominant factor for determining the photobleaching property. This also supports that the photobleaching behavior of YVO 4 :Bi 3+ ,Eu 3+ nanophosphor originates from the photochemical redox reaction between the citrate ions and V 5+ in YVO 4 host crystal and hence the formation of V 4+ and oxygen vacancies, as discussed in our previous work [1]. In addition, the gradual recovery of the normalized PL intensity might be attributed to the oxidation of V 4+ to V 5+ after the photochemical decomposition of citrate ions.…”
Section: Relation Between Citrate Ions and Photobleaching Behaviorsupporting
confidence: 90%
“…A loss of about 80 % of the fluorescence intensity at 617 nm followed by an asymptotic behavior after 10 consecutive UV irradiations occurred. Photobleaching in citrate-derived vanadates has also been reported previously [30]. Takeshita et al showed that surface-complexing citrate anions are involved in the photobleaching process.…”
Section: Photostabilitysupporting
confidence: 62%
“…The colour of the RVO4:Bi materials obtained depends on the sample composition and annealing temperature and varies between white or slightly yellowish to tan. The Y-and Lu-based RVO4:Bi vanadates prepared at 1073 K were white or slightly yellowish, whereas LaVO4:Bi and GdVO4:Bi materials synthesized at 1273 K were brownish evidently due to the partial formation of mixed-valence compounds [17]. It was reported [18] that there is a linear dependence between the intensity of yellow coloration of YVO4 and the EPR signal of V 4+ ion adjacent to an oxygen vacancy.…”
Section: Luminescence and Optical Studies Of The Bi-doped Materialsmentioning
confidence: 95%